Linear and nonlinear representations of Galilei groups in two-dimensional space-time - Lagno, V. I.; Fushchich, V. I. (Ukrains’kyi Matematychnyi Zhurnal, 1998)
We study Galilei groups represented as groups of Lie transformations in the space of two independent variables and one dependent variable. We classify the representations of the groups A G 1(1,1), A G 2(1,1), A G 3(1,1), A G 1 (1,1), A G 2 (1,1), and A G3(1,1) in the class of Lie vector fields.